Survey On Use Of Blockchain Technology In Cloud Storage for The Security Of Healthcare Systems - et. al., Etikala Aruna, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The security has been the need of the hour in health care systems with so much of electronic health records. The cloud not assured to provide security as it is involved the parallel processing and is in distributed nature. The Blockchain (BC) has been introduced in the cloud for some applications like smart healthcare systems since they are highly susceptible on some security violations and several attacks, such as forgery, tampering, privacy leakage, etc. to provide the protection and security for the medical data. Thus a survey on use of Blockchain (BC) technology in cloud storage for the security of healthcare systems is presented in this paper. At first the security measures provided by the traditional cloud storage system are discussed along with its limitations. Then a brief introduction of Blockchain technology in cloud storage with its background work is presented. Finally survey of different works focused on blockchain technology in the healthcare systems is presented as a promising solution for the security issues to provide tightened and enhanced security levels over the health care systems. A potential solution can be provided by this survey with the use of blockchain technology for the protection of healthcare data outsourced over the cloud. By evaluating and comparing the simulation experiments of presented Blockchain technology focused works, it can be prove that a verification of integrity with cloud storage and medical data, data sharing with less computing complexity, and security and privacy protection are achieved.